ApisRAM Formal Model Description. Issue 2 (25th February 2022) - Duan, Xiaodong; Wallis, David; Hatjina, Fani; Simon‐Delso, Noa; Bruun Jensen, Annette; Topping, Christopher John
Abstract: The Apis RAM model is an agent‐based colony model for honey bees in which each bee is modelled as an individual agent. The behaviour of the colony emerges from the decisions and actions taken by individuals in the colony and the interactions between agents. The bees interact with, and react to, both other bees and the resources in the colony, the hive physical and chemical properties, and the environment outside the colony. A key feature of Apis RAM is the approach to representing bee health. This is a 'vitality' model which is used to integrate multiple stressors (unfavourable temperature, food shortage, infectious agents and pesticides) for each individual bee. The vitality of each model bee interacts with all the four stressors. The environment in which the colony is modelled is implemented as a dynamic landscape simulation within ALMaSS (the Animal Landscape and Man Simulation System). The ALMaSS landscape model is a spatially and temporally dynamic model which combines land use, detailed farm practices, weather, crop growth, semi‐natural habitats, and flower resource models. With the combination of the colony and landscape models, the Apis RAM model provides a framework for in silico experiments, e.g., pesticides applications, designed to explore the effects of combined stressors on honey bee colonies under a variety of environmental and human (e.g. beekeeping management practices) factors.